The Components of Happiness: Implications for Retirement Counselling - Stones, M. J.; Kozma, Albert (Canadian Journal of Counselling and Psychotherapy, 2012)
The suggestion is made that retirement be considered the most important criterion dimension of adjustment to retirement. Consequently, the primary function of the retirement counsellor is to promote the happiness of the client. The intention of the present investigationwas to assess the relative contributions to the happiness of elderly people ofthree components of the happiness construct: namely, affect, disposition and the affect x disposition interaction. From this evaluation it was hoped to provide general guidelines forretirement counselling practices. Using scale measures of happiness and its components, three populations of elderly Newfoundland residents and a multiple regression analysisprocedure, the relative contributions of the components to happiness were found to rank: affect > interaction > disposition. Implications for counselling practices arc discussed.